Three Years Retrospective Study of Melanocytic Lesion in Tertiary Hospital: Comparing Benign & Malignant Data - Fitri Ayu Ramadhini (Faculty of Medicine Universitas Indonesia, 2021)
Abstract Melanocytic lesion is defined as skin symptom due to proliferation of melanocytes. It may be considered benign, commonly diagnosed as melanocytic nevus (MN), or may also be malignant as malignant melanoma (MM). Publication of epidemiologic data about melanocytic lesion in Indonesia is limited. The aim of this study was to evaluate the epidemiologic findings of melanocytic lesion based on histopathology and clinical data. This descriptive study was done by collecting retrospective pigmented lesion from histopathology database at Department of Anatomical Pathology dr. Cipto Mangunkusumo National Hospital from 2014 - 2017. Retrieved data were analyzed descriptively for MN and MM include clinical diagnosis, age, sex, location, size and clinical working diagnosis. There were 121 cases of melanocytic lesions consisting of 87.6% MN. Females were more frequent for benign lesions. MN cases were mostly seen at the age below the fourth decade, while from 12 cases of MM found above fourth decade. MN was located mostly on the head and neck, while MM mostly in the lower extremities and soles. There were 75 lesions size and 4 lesions location were unknown data missing. MM is still considered rare. Completing clinical finding in the histopathology request form by surgeons will aid in defining better characteristic of melanocytic lesion in our population. Keyword: epidemiology, melanocytic lesion, nevus melanocytic, malignant melanoma. Studi Retrospektif Lesi Melanositik dalam Tiga Tahun di RS Tersier: Perbandingan Data Jinak dan Ganas Abstrak Lesi melanositik didefinisikan sebagai lesi kulit akibat proliferasi melanosit. Lesi melanositik dapat dianggap jinak, umumnya didiagnosis sebagai nevus melanositik (NM), atau merupakan ganas yaitu melanoma maligna (MM). Publikasi data epidemiologi tentang lesi melanositik di Indonesia masih terbatas. Tujuan dari penelitian ini adalah untuk melakukan evaluasi gambaran epidemiologis lesi melanositik berdasarkan data histopatologi dan klinis. Penelitian deskriptif ini dilakukan dengan mengumpulkan data retrospektif lesi berpigmen dari basis data histopatologi di Departemen Patologi Anatomi Rumah Sakit Nasional dr. Cipto Mangunkusumo dari tahun 2014 - 2017. Data dianalisis secara deskriptif untuk NM dan MM termasuk diagnosis kerja, usia, jenis kelamin, lokasi, ukuran, dan diagnosis klinis. Terdapat 121 kasus lesi melanositik yang terdiri atas 87,6% NM. Lesi jinak lebih banyak ditemukan pada wanita. Terdapat 75 dan 4 kasus dengan data ukuran lesi dan lokasi tidak tercantum. MM masih dianggap jarang. Kasus NM sebagian besar terlihat pada usia di bawah dekade keempat, sedangkan dari 12 kasus MM di atas dekade keempat. NM sebagian besar terletak di kepala dan leher, sedangkan MM ditemukan di ekstremitas bawah dan telapak kaki. Melengkapi temuan klinis dalam formulir permintaan histopatologi oleh dokter bedah akan membantu dalam menentukan karakteristik lesi melanositik lebih baik pada populasi ini. Kata kunci: epidemiologi, lesi melanositik, nevus melanositik, melanoma maligna